Paradygmat podmiotowości – refleksje pedagogiczne - Jusiak, Roman (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The person as a subject paradigm is gaining in importance nowadays. Subjectivity is a fundamental desideratum in social sciences, especially in pedagogy. The category “subjectivity” is defined in different ways. Most often it is understood as a personal and social value or as a social ideal and the assumption of social ontologies, as well as an assumption about the primacy of subjectively active individuals in relation to the social structure. This type of issue is taken up by various disciplines. First of all, by philosophy, psychology, sociology and pedagogy. Among various philosophical concepts, it is worth paying special attention to personalism, which interprets man and the whole reality in the context of the phenomenon of the human person. Psychology emphasizes that man is the subject of his activity when he is autonomous towards the environment and consciously influences the external world. Psychology analyzes also various internal determinations of the human person. Pedagogy treats the issue of subjectivity as an idea, value, goal and postulate of educational activity, something that should be achieved. The development of one’s own subjectivity is important for every human being. A person, in order to function in a subjective way, should properly shape his personality. The task of educators is to help individuals in shaping their own subjectivity and self-reliance.